Aplikasi Booking Online Make Up Artist di Surabaya Berbasis Mobile - Thomas Kevin Wijoyo; Kristo Radion Purba (Jurnal Infra, 2018)
Make Up Artist is one of the services by doing make over the women to make it look more beautiful and different. MUA in Indonesia uses several social media applications in transacting like Instagram, Facebook, and Line. But there are some obstacles that are often experienced by users such as schedule settings because many clients are asking on the same day, difficulty in searching MUA around the location and searching manual which takes a long time because using hashtag in instagram so have to open one by one.To solve the problem, there is a solution by creating an online booking application, where users can more easily find MUA. Make UP 4U application has a search feature that makes it easier for users to search for MUA on both empty date search and nearby location.Based on the results of the questionnaire, in the user section (tenant) 80% of respondents rated. For review feature reviews &ratings, 80% of respondents are rated well. For the search feature assessment, 60% of respondents rated well. For assessment of booking notification feature in the form of email 60% of respondents rated well. For a valuation of ease using the application 100% of respondents rated well. For the assessment of conformity with the needs, 100% of respondents value well.